A comprehensive review on the use of traditional Chinese medicine for cancer treatment - Neha Yadav; Rohitas Deshmukh; Rupa Mazumder (Elsevier, 2024)
Introduction: Healthcare in China has historically relied on Traditional Chinese Medicine (TCM), which has had far-reaching effects on healthcare systems in neighboring nations. TCM has generated anticancer herbal medications. Cancer clinical trials have also examined herbal remedies. Methodology: Web of Science, Scopus, PubMed, and Google Scholar were among the online databases that were searched. Consequently, this review set out to compile a synopsis of the documented phytochemistry and pharmacological activities of the selected plant species. This literature review sought to illuminate TCMadjuvant cancer therapeutic role. New research reveals herbal medicines may inhibit cancer cell migration, adhesion, proliferation, and death. Results: This review aimed to summarise herbs and their TCM processes for chemoprevention and treatment. TCM treatments that target cancer stem cells and alter the tumor microenvironment have also been studied. This review will underpin traditional Chinese medicine cancer therapy research. Discussion: The bioactive chemicals in these herbs have been shown in clinical trials to have a wide range of cancer-fighting properties, with few side effects and a marked improvement in patient's quality of life. Conclusion: Given these benefits, it's clear that incorporating Chinese medicines into cancer care could be a significant step towards a more effective and comprehensive approach to treating the disease.